Effect of Sex, Age and Agro-climatic Zone on Carcass and Meat Quality Traits of Black Bengal Goats - Sikder, Sujoy Kumar; Chatterjee, J. K.; Biswas, S.; Das, S.; Biswas, A. K. (Journal of Meat Science, 2017)
The aim of this study was to evaluate the effect of sex, age and agro-climatic Zone on carcass quality traits and meat quality parameter of Black Bengal goats reared under extensive managerial practices at farmers door step. For this, both male and female goat of four different age groups (0 – 3, 3 – 6, 6 – 9 and 9 – 12 months and above) were selected from four Agro-climatic Zones viz. Teesta Alluvial, Gangetic Alluvial, Undulating Red and Lateritic and Coastal Saline zones of West Bengal and different carcass quality traits and meat quality parameters were evaluated. Results indicated that birth weight had direct influence on body weight gain irrespective of sex or origin of animals. In general, pH, cholesterol, protein, ether extract and ash contents were increased while moisture contents were decreased in meat from both male and female goats with the inclement of age. Sensory quality of the selected goat meat samples was affected by the age but not by the sex and zones. In conclusion, sex and agro-climatic zones showed little or no significant effect on carcass quality traits, but age has significant influence on meat quality attributes irrespective of sex and agro-climatic zones.
Keywords: Black Bengal Goat; Carcass traits; Meat quality; Agro climatic zone